An anti-biodegradable hydrophobic sulfonate-based acrylamide copolymer containing 2, 4-dichlorophenoxy for enhanced oil recovery. (28th September 2015) - Gou, Shaohua; He, Yang; Zhou, Lihua; Zhao, Peng; Zhang, Qin; Li, Shiwei; Guo, Qipeng
Abstract : We report the synthesis of a novel hydrophobic sulfonate-based acrylamide copolymer which exhibits remarkable water solubility, excellent resistance to biodegradability, and superior ability to enhance oil recovery. Abstract : We report here a novel anti-biodegradable hydrophobic acrylamide copolymer that was prepared from acrylamide, acrylic acid, sodium 3-(allyloxy)-2-hydroxypropane-1-sulfonate and N -allyl-2-(2, 4-dichlorophenoxy) acetamide using the 2, 2′-azobis(2-methylpropionamide) dihydrochloride initiation system. Subsequently, the copolymer was characterized by FT-IR, 1 H NMR, TG-DTG and water-solubility. And the biodegradability test indicated that the copolymer was not deemed to be readily biodegradable via a closed bottle test established by the Organization for Economic Co-operation and Development (OECD 301 D). Meanwhile the copolymer could significantly enhance the viscosity of the aqueous solution in comparison with partially hydrolyzed polyacrylamide. A viscosity retention of 51.9% indicated the result of a dramatic improvement of temperature tolerance. And then the excellent salt resistance, shear resistance, viscoelasticity, long-term stability of the copolymer could be obtained, which provides a good theoretical foundation for the application in enhanced oil recovery. In addition, this copolymer exerted stronger mobility control ability with a resistance factor of 22.1 and a residual resistance factor of 5.0, and superior ability for enhanced oil recovery of 12.9%. Hence, the copolymer has potential application for enhanced oil recovery in high-temperature and high-salinity reservoirs.